Pengaruh Penerapan Strategi Segmentasi, Penentuan Target Pasar, dan Posisi Merek (STP) serta Personal Selling terhadap Peningkatan Penjualan Aspal di PT Sarana Aceh Utama - Vilzati; Andi Roza, T.; Marlina, Leni; Tedy Kelana (Jurnal EMT KITA, 2025)
Increasingly fierce business competition requires companies to implement the right marketing strategies to maintain and increase sales volume. This study aims to analyze the influence of Segmentation, Targeting, and Positioning (STP) strategies and personal selling on increasing sales at PT. Aceh Main Facilities. This study uses a quantitative approach with a survey method, where primary data is collected through questionnaires to 35 respondents from the marketing, finance, and operational divisions. The sampling technique used is purposive sampling. Validity and reliability testing shows that the research instrument is valid and reliable. Multiple linear regression analysis showed that both STP (β = 0.721; sig. < 0.05) and personal selling (β = 0.531; sig. < 0.05) had a positive and significant effect on sales. Simultaneously, these two variables contributed 62% to the sales variation (Adjusted R² = 0.620). These results indicate that the implementation of the right STP strategy and the implementation of effective personal selling can increase the company's competitiveness and sales in the market. This research suggests the importance of strengthening segmentation-based marketing strategies and personalized approaches to maintain market position.
Keywords: STP Strategy; Personal Selling; Sales; Marketing; PT. Aceh Main Facilities